Rethinking teacher training: Covid-19 and the rise of e-learning - Soler Costa, Rebecca; Lafarga Ostáriz, Pablo (Wydawnictwo Uniwersytetu Rzeszowskiego, 2020)
He Covid-19 pandemic has caused an exponential change in the educational environment. The impact of epidemiological situation has been so powerful, that it can be considered that a new paradigm has been born based on semi-presence as new didactic normality. We witness the new and accelerated context where Information and Communication Technologies (ICT) have acquired a greater role than they used to ever have. Under this new perspective, which also involves a strong reflection on the teaching-learning processes, a review of existing technological resources and their functionality at present is proposed. Taking all of this into consideration, during the beginning of the 21st century the technological advances in the field of education have been significant. Management platforms, resources on the Internet, or other media and simultaneous interaction are some of the key tools in a world immersed in a rethinking that goes far beyond a classroom.

Pandemia Covid-19 spowodowała ogromną zmianę w środowisku edukacyjnym. Wpływ sytuacji epidemiologicznej był tak silny, że można uznać, iż powstał nowy paradygmat oparty na „półobecności” jako nowej normie dydaktycznej. Jesteśmy świadkami nowego kontekstu, w którym technologie informacyjne i komunikacyjne (ICT) zyskały większą rolę niż kiedykolwiek. W tej nowej perspektywie, która obejmuje również silną refleksję nad procesami nauczania i uczenia się, proponuje się przegląd istniejących zasobów technologicznych i ich aktualnej funkcjonalności. Biorąc pod uwagę powyższe, na początku XXI wieku postęp technologiczny w dziedzinie edukacji był bardzo znaczący. Platformy zarządzania, zasoby Internetowe lub inne media i interakcja symultaniczna to tylko niektóre z kluczowych narzędzi w świecie objętym rewolucyjnym podejściem do nauczania, które wykraczają daleko poza salę lekcyjną.
Nowe podejście do szkolenia nauczycieli: Covid-19 i rozwój e-learningu
Keywords: e-learning; digital competence; higher education; ICTs; kompetencje cyfrowe; szkolnictwo wyższe; technologie informacyjne i komunikacyjne